The competitiveness of ports on the periphery: what could be done? - Ismail, Alisha (GBSE, 2019)
There is abundant research into the competitiveness of maritime transportation and the port industry in general. In addition, previous and current researches apparently prone to investigate the competitiveness and performance of large size of ports that hold international and regional hub status. Of these studies, it is interesting to note that there is scarce study in the smaller size of ports, in particular the ones that have disadvantage in term of location. In the literature, the study of the small size of ports is more focusing on its development only. However, there is little research into how to make small size of port or ‘ports on the periphery’ more competitive although they face particularly strong threats in a highly competitive environment. Thus, gap is identified. More importantly, in enhancing the competitiveness and subsequently the performance of this category of ports, this study also proposing spatial characteristics, port supply chain integration and sustainability advantages are seen as the promising strategies that able to assist the ports to compete with other adjacent small or large ports.